2022
DOI: 10.3390/coatings12030397
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Defects and Heteroatoms on the Chemical Properties of Supported Graphene Layers

Abstract: A large and growing number of theoretical papers report the possible role of defects and heteroatoms on the chemical properties of single-layer graphene. Indeed, they are expected to modify the electronic structure of the graphene film, allow for chemisorption of different species, and enable more effective functionalisation. Therefore, from theoretical studies, we get the suggestion that single and double vacancies, Stone–Wales defects and heteroatoms are suitable candidates to turn nearly chemically inert gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The defected graphene overlayer increased the sensitivity to water and toluene. This agrees with recent calculations showing that toluene [43] and water [47,48] adsorb better to graphene with defects. In comparison, exposure to ethanol and 2-propanol resulted in similar optical responses, while acetone even gave a reduced signal on defected graphene.…”
Section: Resultssupporting
confidence: 93%
“…The defected graphene overlayer increased the sensitivity to water and toluene. This agrees with recent calculations showing that toluene [43] and water [47,48] adsorb better to graphene with defects. In comparison, exposure to ethanol and 2-propanol resulted in similar optical responses, while acetone even gave a reduced signal on defected graphene.…”
Section: Resultssupporting
confidence: 93%
“…[ 96 ] Earlier (in 2022), a detailed study on the effect of the defects and heteroatoms on the chemical features of supported graphene layers was reported by Vattuone and co‐workers. [ 97 ]…”
Section: Influence Of Sw Defect On Properties Of Graphenementioning
confidence: 99%
“…In some previous studies on VRD reactors, it was reported that the inlet flow affected the film deposition rate and film thickness uniformity [26]. A simplified rotation model was developed by Makino et al; from the reaction model of deposition of Si in a gas mixture of SiHCl 3 -H 2 , the effect of gas flow on the deposition rate of silicon in a VRD reactor was studied according to the method of the normalized central moment [8]. Both Coltrin and Makino proposed a moderate flow rate (about 90 SLM (standard liters per minute)) as "the ideal inlet velocity of the disk" [27].…”
Section: Influence Of Intake Flow Rate On Graphene Deposition Ratementioning
confidence: 99%
“…Among them, the chemical vapor deposition (CVD) method has the advantages of high quality, large area, controllable layer number, good repeatability, and low cost, which is expected to achieve large-scale industrial preparation of graphene and has obtained the continuous attention and exploration of scientific research workers. The CVD process of graphene growth involves a series of complex gas-phase surface chemical reactions, generally through three processes [8,9]: gas phase decomposition, surface chemical reaction, and gas phase diffusion. The complexity of graphene growth by CVD is that it involves not only chemical reactions but also mass, momentum, and energy transfer.…”
Section: Introductionmentioning
confidence: 99%